2005
DOI: 10.1212/01.wnl.0000168837.87351.1f
|View full text |Cite
|
Sign up to set email alerts
|

Brain atrophy and lesion load in a large population of patients with multiple sclerosis

Abstract: Patients with multiple sclerosis have significant atrophy of both white matter (WM) and gray matter (GM); secondary progressive patients have significantly more atrophy of both WM and GM than do relapsing-remitting patients and a significantly higher lesion load (abnormal WM fraction); lesion load is related to both WM and even more to GM atrophy; lesion load and WM and GM atrophy are significantly related to Expanded Disability Status Scale score and age at onset (suggesting that the younger the age at diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
132
2
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(146 citation statements)
references
References 23 publications
11
132
2
1
Order By: Relevance
“…Consequently, future research should directly identify possible links between underlying MS-related neuropathology, not only with facial affect recognition, but also with ToM. This seems particularly important given that, although white matter pathology is the primary neurological feature of MS, demyelination in cortical gray matter is also observed to a variable extent, and the focality of demyelinating lesions in MS can vary widely (Filley 2005 ;Tedeschi et al, 2005 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Consequently, future research should directly identify possible links between underlying MS-related neuropathology, not only with facial affect recognition, but also with ToM. This seems particularly important given that, although white matter pathology is the primary neurological feature of MS, demyelination in cortical gray matter is also observed to a variable extent, and the focality of demyelinating lesions in MS can vary widely (Filley 2005 ;Tedeschi et al, 2005 ).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Although being male has been proposed as a risk factor for cognitive impairment in MS patients [5], the results on brain neuropathological MS indices are conflicting, some studies have suggested a higher degree of brain damage in males [6][7][8], while others have failed to replicate these findings [9,10]. As these conflicting results might derive from gender interacting with other relevant demographic and clinical variables, we explored whether female and male MS patients, carefully matched for age, years of disease, level of education, intelligence quotient (IQ), neuropsychological performance and physical disability, differed in two indices of MS progression: gray matter (GM) atrophy and resting state functional connectivity (FC) changes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the extension and pathological basis of GM pathology have been highlighted from pathological and neuroimaging studies [8]. GM atrophy, extensively reported in MS, begins early and evolves over the course of the disease, and GM tissue volumes are lower in MS patients than in control subjects [9][10][11][12][13][14][15]. The study of GM damage is of critical importance since axonal and neuronal damage are the main factors responsible for long-term disability in MS.…”
Section: Introductionmentioning
confidence: 99%